Faktor-Faktor yang Mempengaruhi Perilaku Belajar Mahasiswa dengan Menggunakan Pendekatan Partial Least Square-Structural Equation Modeling (Pls-Sem) Analysis - Darul Wiyono; Nur Ahmad Ruyani (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
In the higher educational institutions, the behaviour of the students need to be managed and members of the institutions are required to bring about improvements in the implementation of tasks and functions. Learning behavior is influenced by several factors, including internal factors, namely physical, psychological, motivational, and external factors, namely the environment. This study aims to analyze the factors that influence student learning behavior in terms of family environment factors, campus environment, and motivation to learn. The type of research is descriptive using explanatory survey research methods, this study will be analyzed using structural equation models (Structural Equation Modeling, SEM) with alternative Partial Least Square (PLS) methods using SmartPLS 3.0 software. The population of this study was the students of ASM Ariyanti Bandung. The results of testing the first hypothesis showed that there was a significant correlation between the family environment and the campus environment. The second hypothesis has a significant correlation between campus environment and learning motivation. The third hypothesis also has a significant correlation between family and environment and motivation to learn. The results of the fourth hypothesis indicate that the family environment has a positive and significant effect on student learning behavior. The fifth hypothesis shows that the campus environment has a positive and significant effect on student learning behavior. The sixth hypothesis shows that learning motivation has a positive and significant effect on student learning behavior. The seventh hypothesis shows that the family environment, campus environment, and motivation to learn together have a positive and significant effect on student learning behavior. So it is clear that the family environment, campus environment, learning motivation and student learning behavior are interconnected. This must be considered because there are interplay between these four factors. Keywords: Family Environment, Campus Environment, Learning Motivation, Student Learning Behavior.